Legal Adaptation of Crimes Arising from Climate Change–Related Disasters - Adnan, Mohammad E. (PROSPECTIVE RESEARCHES, 2026)
This research examines the interactive relationship between climatic and environmental disasters, on the one hand, the increase in crime rates and the transformation of crime patterns. However, within an international legal framework that highlights the challenges of responsibility, accountability, and the effectiveness of existing legal rules. Recent studies have demonstrated that natural and climate related disasters such as floods, droughts, and rising temperatures not only cause environmental and economic damage but also contribute to the creation of fragile social environments that lead to higher crime rates. This includes traditional crimes associated with disturbances of public order, as well as newly emerging crimes resulting from the exploitation of emergency situations and weakened institutional oversight. Within this context, the research highlights crimes against nature as one of the direct and indirect causes of natural and climatic disasters, including environmental pollution offenses, illegal deforestation, and the excessive exploitation of natural resources, all of which lead to ecological imbalance and the intensification of extreme climatic phenomena The study emphasizes that such crimes are no longer purely domestic in nature, but have come to constitute transboundary threats that affect the collective interests of the international community. The research concludes with an analysis of the legal classification of crimes committed during natural disasters, demonstrating that the exceptional circumstances imposed by such disasters necessitate a reconsideration of certain traditional concepts of criminal responsibility. This includes the aggravation of penalties for crimes that exploit disaster situations, as well as the recognition of mitigating legal excuses in cases of extreme necessity Ultimately, the study underscores the need to develop a comprehensive international legal framework that links environmental protection, criminal justice, and disaster management, thereby ensuring a more effective legal response to contemporary climate challenges.